2007
DOI: 10.1136/bmj.39136.528160.be
|View full text |Cite
|
Sign up to set email alerts
|

Oral decontamination for prevention of pneumonia in mechanically ventilated adults: systematic review and meta-analysis

Abstract: Objective To evaluate the effect of oral decontamination on the incidence of ventilator associated pneumonia and mortality in mechanically ventilated adults. Design Systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
214
0
29

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(248 citation statements)
references
References 44 publications
5
214
0
29
Order By: Relevance
“…The use of broad-spectrum systemic antibiotics with little anaerobicidal activity for 2 to 4 days seems to be a crucial part of SID schedules for critical patients and has led to the best reported results in terms of the reduction of the incidence of bacterial infections, 6,21,22 so this strategy could also be beneficial to LTRs, at least during the ICU admission after transplantation. Our data also confirm the importance of other previously reported risk factors for EBIs, such as biliary-enteric hepaticojejunostomy, early surgical graft complications, acute rejection, and early renal failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of broad-spectrum systemic antibiotics with little anaerobicidal activity for 2 to 4 days seems to be a crucial part of SID schedules for critical patients and has led to the best reported results in terms of the reduction of the incidence of bacterial infections, 6,21,22 so this strategy could also be beneficial to LTRs, at least during the ICU admission after transplantation. Our data also confirm the importance of other previously reported risk factors for EBIs, such as biliary-enteric hepaticojejunostomy, early surgical graft complications, acute rejection, and early renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…the use of topical or nonabsorbable antibiotics, could be useful in this population because of their demonstrated efficacy in other critical patients and the low risk for the selection of resistant strains. 6,21,22 New nonabsorbable antibiotics specifically designed for SID, such as rifaximin, should be analyzed in this population, mostly because of the promising results of this drug in the prevention of encephalopathy in patients with cirrhosis. 26,27 Finally, preliminary results suggest that nonantibiotic SID strategies, such as the use of probiotics or prebiotics, could be useful in the prevention of EBIs in LTRs.…”
Section: Discussionmentioning
confidence: 99%
“…One trial did report a decrease in mortality [67] and one reported a decrease in duration of hospitalization [66], but these findings were not borne out by the other nine studies. A meta-ana lysis including the six trials published through 2007 suggested a net 44% decrease in VAP rates but no decreases in patients' ventilator days, hospital days or mortality [75].…”
Section: Oral Antiseptics and Antibioticsmentioning
confidence: 99%
“…16 As the number of immunocompromised individuals in the population continues to increase, so too does the incidence of mucosal infections in the mouth, in particular oral candidosis. Given the concern over the emergence of resistance of yeasts to systemic antifungal agents, there is a clinical requirement for new and effective topical anticandidal strategies.…”
Section: Introductionmentioning
confidence: 99%